CCAFS Organisational Baseline Study 2012 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
In 2012, CCAFS undertook organisational-level baseline studies at 15 core sites in Eastern Africa, West Africa and South Asia. These studies were to supplement the quantitative household baseline surveys and qualitative village baseline studies at the same locations. The aim of the organisational baseline was to provide information about the provision of services and agricultural/climatic information by organisations operating in the locality. This study contains the study "pack" (questionnaire & guidelines) as well as the results from each site.